The persistence of the gender earnings gap: Cohort trends and the role of education in twelve countries - Eyal Bar-Haim; Louis Chauvel; Janet C. Gornick; Anne Hartung (Luxembourg Income Study (LIS), 2018)
Studying twelve countries over 30 years, we examine whether women's educational expansion has translated into a closing gender earnings gap. As educational attainment is cohortdependent, an Age-Period-Cohort analysis is most appropriate in our view. Using the Luxembourg Income Study (LIS) data, we show that while in terms of attainment of tertiary education women have caught up and often even outperform men, substantial gender differences in earnings persist in all countries. These results are consistent with the composition of the top earnings decile. Using Blinder-Oaxaca decomposition methods, we demonstrate that the role of education in explaining the gender earnings gap has been limited and even decreased over cohorts. Contrary, employment status as well as occupation explain a more substantial part in all countries. We conclude that earnings differences at levels far from gender equality likely also persist in the future, even if the "rise of women" in terms of education continues.
Keywords: J31; J7; I26; N30; 330; gender gap; education; earnings; age-period-cohort analysis; Blinder-Oaxaca decomposition